2014
DOI: 10.1097/inf.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Single Virus and Viral Coinfections on Severe Lower Respiratory Tract Infections Among Preterm Infants

Abstract: This study confirms the association of RSV alone or as a coinfection with severe LRTI and reinforces the importance of providing adequate prophylaxis for susceptible infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 53 publications
4
28
2
7
Order By: Relevance
“…Thirty‐four studies from 26 countries that were published between 2002 and 2014, with RSV‐associated ARI hospitalization rates for community‐acquired, medically attended, laboratory‐confirmed severe RSV‐ARI in children <5 years of age, were included in the incidence analysis. The incidence estimates of RSV‐associated ARI hospitalization (per 1,000 children per year) were stratified according to age and region (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐four studies from 26 countries that were published between 2002 and 2014, with RSV‐associated ARI hospitalization rates for community‐acquired, medically attended, laboratory‐confirmed severe RSV‐ARI in children <5 years of age, were included in the incidence analysis. The incidence estimates of RSV‐associated ARI hospitalization (per 1,000 children per year) were stratified according to age and region (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies carried out in the United States show lower hospitalization rates in preterm infants than those reported in previous analyses . Also, the incidence of RSV‐associated hospitalization varies in studies carried out in different countries . In a systematic review that assessed the incidence of RSV hospitalization in healthy preterm infants 29‐35 weeks of age, a wide variation of in hospitalization rates (2.3%‐10%) was observed .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the studies included in the main analysis, such as age, prevalence of coinfection, setting of enrollment, viruses tested through molecular biology techniques, specific combinations of viruses compared and outcomes assessed. Forty-three studies with 17234 patients were included [6,[8][9][10][12][13][14][15][16][17][18][19]21,. Final analyses included the following outcomes: length of stay (24 studies, 3548 patients), need of hospitalization (11 studies, 9637 patients), need of supplemental oxygen (12 studies, 2285 patients) and length of supplemental oxygen (5 Table 2 Summary of findings and quality of evidence for severity of viral coinfections versus single infections in children.…”
Section: Study Selectionmentioning
confidence: 99%
“…The relationship between detection of multiple respiratory viral infections and severity of disease in children has not been well established. Several studies have reported longer length of stay in hospital, an increased risk of hospitalizations, of admission to pediatric intensive care unit (PICU), of need for mechanical ventilation and even higher mortality, when two or more respiratory viruses were detected [11][12][13][14][15][16][17].…”
mentioning
confidence: 99%